Peningkatan Literasi Digital untuk Menangkal Hoaks pada Siswa SMP - Putri Arini, Diana; Agung Pramudito, Anselmus; Riyanto, Riyanto; Sukarman , Sukarman (Indonesian Journal for Social Responsibility, 2023)
Students are vulnerable group to being provoked by hoax news, this is because their thinking and emotional management skills are still immature. Hoax reporting has an impact on prejudice, hostility between groups and problems managing emotions due to accessing hate news. The aim of this activity is to increase digital literacy among students and provide journalistic training so that students are able to use social media healthily and avoid hoax news. The implementation was carried out at the private school SMP Teachers also admit that students often don't focus in class because they use their cellphones to check social media or play games. The activities provided were conducting digital literacy education and journalism training for 23 junior high school students. Measurements were carried out by assessing the results of the Pre-Test and posttest regarding digital literacy material, assignment of news writing tasks and participant satisfaction. The results show that there is a very significant increase in students' digital literacy knowledge. The level of student satisfaction with activities is in the good category. Suggestions for development for further activities include monitoring digital literacy regarding the use of social media.